Bright and dark vessels on stroke imaging: different sides of the same coin? - Vural, Atay; Gocmen, Rahsan; Oguz, Kader Karli; Topcuoglu, Mehmet Akif; Arsava, Ethem Murat (Diagnostic & Interventional Radiology)
Purpose: Prominent hypointense cerebral vessels on susceptibility-weighted imaging (SWI) and the hyperintense vessel sign (HVS) on fluid-attenuated inversion recovery (FLAIR) imaging are considered as markers of compromised tissue perfusion in cerebral ischemia. In this study, we aimed to identify the correlation between HVS on FLAIR and hypointense vessels on SWI, and to determine whether these imaging features provide independent prognostic information in patients with ischemic stroke.Methods: We retrospectively analyzed consecutive ischemic stroke patients with proximal middle cerebral artery (MCA) occlusion who underwent SWI and FLAIR within 24 h of symptom onset. The presence of hypointense vessels on SWI and hyperintense vessels on FLAIR in >4 of 10 slices encompassing the MCA territory were considered to represent prominent hypoperfusion.Results: Among 50 patients, 62% had a prominent HVS on FLAIR and 68% had prominent hypointense vessels on SWI. There was a moderate but significant correlation between the number of slices with HVS on FLAIR and prominent hypointense vessels on SWI (r=0.425, P = 0.002). In multivariate analyses, the prominence of hypointense vessels on SWI, but not HVS on FLAIR, was significantly associated with a higher discharge NIHSS score (P = 0.027), mRS score (P = 0.021), and lesion growth (P = 0.050).Conclusion: The significant, albeit moderate, correlation between markers of compromised tissue perfusion on FLAIR and SWI suggests that these imaging features reflect different but interrelated aspects of cerebral hemodynamics during ischemic stroke. Our findings highlight that while HVS on FLAIR denotes the presence of leptomeningeal collaterals, hypointense vessels on SWI signify the sufficiency of cerebral blood flow at the tissue level and are therefore more critical in terms of prognosis.